2022
DOI: 10.1002/2688-8319.12141
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the effects of habitat aridity, evolutionary history of grazing and grazing intensity on bee and butterfly communities worldwide

Abstract: A variety of habitat‐associated factors moderate effects of grazing on insect biodiversity. Here, we examine how aridity, evolutionary history of grazing and grazing intensity individually and interactively mediate the effect of livestock grazing on pollinator biodiversity (native bees and butterflies). Using a meta‐analysis of 59 studies published in the primary literature, we characterized the response of pollinator communities to grazing across several continents. In very humid habitats, high grazing intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In the United States, one study found cattle‐grazed pastures had higher butterfly species richness and diversity than sheep‐grazed pastures (Cutter et al 2022). Humidity may explain regional differences in effects of grazing intensity on butterfly communities, with butterflies in higher humidity areas being more adversely affected by high grazing intensity than butterflies in more arid areas (Thapa‐Magar et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, one study found cattle‐grazed pastures had higher butterfly species richness and diversity than sheep‐grazed pastures (Cutter et al 2022). Humidity may explain regional differences in effects of grazing intensity on butterfly communities, with butterflies in higher humidity areas being more adversely affected by high grazing intensity than butterflies in more arid areas (Thapa‐Magar et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The variability in responses of native bees to livestock grazing may be due to myriad factors, including differences in the type of grazer, the intensity of grazing, the timing of grazing, plant growth stage, and the species traits of the particular bee species in the system ( Kimoto et al 2012b ;Cutter et al, 2021 ). Several recent reviews suggest that the variability of insect pollinator responses to grazing may be mediated by the evolutionary history and habitat traits of a given system, with overall negative effects on pollinator abundance and richness ( Glenny et al 2022 ;Thapa-Magar et al 2022 ), especially in regions that lack long-term evolutionary histories with herds of large mammalian grazers ( Thapa-Magar et al 2022 ). These effects may occur through multiple pathways, including dietary overlap (i.e., livestock and bees consuming the same floral resources) ( DeBano et al 2016 ), degrading nesting resources through soil and vegetation trampling ( Kurz et al 2006 ;Kimoto et al 2012b ;Schmalz et al 2013 ), and by changing bee foraging behavior ( Sjödin 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The accurate and timely measurement of pasture is an integral part of eective grazing management (French et al 2015), which could be provided by the use of remote sensing. Thapa-Magar et al (2022) suggest that (negative) eects of livestock grazing on pollinator communities may be driven by the impact on nesting habitats due to variables such as soil compaction. Soil compaction in pasture use is associated with highly frequently visited places.…”
Section: Gps Position Data For Continuously Monitoring the Behaviour ...mentioning
confidence: 99%